Two flavonoids first isolated from the seed of Syzygium nervosum and preliminary study of their anticancer and anti-HIV-1 reverse transcriptase activities - Chailungka A. (2017)
© 2017 by Maejo University, San Sai, Chiang Mai, 50290 Thailand. Two flavonoids, viz. 2′,4′-dihydroxy-6′-methoxy-3′,5′-dimethylchalcone (DMC) and hariganetin were first isolated from the dichloromethane extract of the seed of Syzygium nervosum and their biological activities against cancer cell lines and HIV-1 reverse transcriptase were preliminary studied. Both DMC and hariganetin show moderate activities against HIV-1 reverse transcriptase with 67.5% and 64.1% inhibition respectively.